2012
DOI: 10.1177/0269215512442669
|View full text |Cite
|
Sign up to set email alerts
|

Patient-focused goal planning process and outcome after spinal cord injury rehabilitation: quantitative and qualitative audit

Abstract: The findings of this clinical audit underpin the need for patient-focused goal planning rehabilitation programmes which are tailored to the individual's needs and involve a comprehensive multidisciplinary team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 19 publications
4
48
0
Order By: Relevance
“…However, previous studies of patient participation have not reported scheduled goal-setting meetings as a requisite as clearly as this study does. Goalsetting meetings and checklists aimed to enhance that the patient's active participation are well established in SCI rehabilitation [9,10]. Such routines, together with the acknowledgement of the patient as a team member may be transferable and useful for other settings to enhance person centeredness and patient participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies of patient participation have not reported scheduled goal-setting meetings as a requisite as clearly as this study does. Goalsetting meetings and checklists aimed to enhance that the patient's active participation are well established in SCI rehabilitation [9,10]. Such routines, together with the acknowledgement of the patient as a team member may be transferable and useful for other settings to enhance person centeredness and patient participation.…”
Section: Discussionmentioning
confidence: 99%
“…Patient participation is also central to achieve high-quality person-centered care [5,6], and has been found to be associated with improved self-care [7,8], better physical functioning [9,10], and satisfaction with care [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Planning and setting goals is a well-developed and well-used strategy in rehabilitation, wherein the patient's participation is nonarguable. 6,11,34,39,[48][49][50][51][52][53] (The patient should be active in defining his or her needs, what important goals and outcomes are, as well as priority and weight different outcomes. 6,50,51 However, the patient needs help and coaching in this process.…”
Section: Specific Use Of the Concept Patient Participationmentioning
confidence: 99%
“…4 Goal setting is about negotiation and an agreement between the patient and the RPs is sought. 4,11,49,53 Setting goals and priorities is a type of shared decision-making that occurs in rehabilitation. 54,55 Mirjam Körner 55 refers to shared decision-making as an ideal model for the patient's participation.…”
Section: Specific Use Of the Concept Patient Participationmentioning
confidence: 99%
See 1 more Smart Citation